2023
DOI: 10.1002/smll.202301201
|View full text |Cite
|
Sign up to set email alerts
|

Lung Persistence, Biodegradation, and Elimination of Graphene‐Based Materials are Predominantly Size‐Dependent and Mediated by Alveolar Phagocytes

Abstract: Graphene‐based materials (GBMs) have promising applications in various sectors, including pulmonary nanomedicine. Nevertheless, the influence of GBM physicochemical characteristics on their fate and impact in lung has not been thoroughly addressed. To fill this gap, the biological response, distribution, and bio‐persistence of four different GBMs in mouse lungs up to 28 days after single oropharyngeal aspiration are investigated. None of the GBMs, varying in size (large versus small) and carbon to oxygen ratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 70 publications
4
16
0
Order By: Relevance
“…Overall, the striking contrast between high aspect ratio BNNTs and low aspect ratio h-BN effects highlights their main physical difference, i.e., their dimensional aspect ratio, as the leading cause of their toxicity, in a similar fashion to what was reported before for carbon-based materials when comparing long and rigid carbon nanotubes with small dimension graphene nanoplatelets or GO. 26,27,35 In a comparable study to ours, Xin et al reported acute and chronic adverse effects after pharyngeal aspiration to 40 μg of BNNTs. 11 In line with our findings, they found an influx in neutrophils and eosinophils as well as the presence of lymphocytes in BALF.…”
Section: Resultssupporting
confidence: 76%
See 4 more Smart Citations
“…Overall, the striking contrast between high aspect ratio BNNTs and low aspect ratio h-BN effects highlights their main physical difference, i.e., their dimensional aspect ratio, as the leading cause of their toxicity, in a similar fashion to what was reported before for carbon-based materials when comparing long and rigid carbon nanotubes with small dimension graphene nanoplatelets or GO. 26,27,35 In a comparable study to ours, Xin et al reported acute and chronic adverse effects after pharyngeal aspiration to 40 μg of BNNTs. 11 In line with our findings, they found an influx in neutrophils and eosinophils as well as the presence of lymphocytes in BALF.…”
Section: Resultssupporting
confidence: 76%
“…Overall, the striking contrast between high aspect ratio BNNTs and low aspect ratio h -BN effects highlights their main physical difference, i.e. , their dimensional aspect ratio, as the leading cause of their toxicity, in a similar fashion to what was reported before for carbon-based materials when comparing long and rigid carbon nanotubes with small dimension graphene nanoplatelets or GO. ,, …”
Section: Resultssupporting
confidence: 75%
See 3 more Smart Citations